VALIDATION OF CYCLAMATE ANALYSIS METHOD WITH SPECTROPHOTOMETRY AND TURBIDIMETRY - Regina Tutik Padmaningrum; Siti Marwati (Jurnal Sains Dasar, 2015)
This research aims to validate methods of analysis by spectrophotometry and turbidimetry cyclamate in the sample drink mango-flavored jelly drink  by spectrophotometry with hypochlorite reagent, ultraviolet spectrophotometry (without reagent) and turbidimetry. The object of research was the validity parameters spectrophotometric method were linearity, linear range, the limit of detection, limit of quantitation, precision, and accuracy. The calibration curve of standard solution of sodium cyclamate in the spectrophotometric method with hypochlorite reagent, UV spectrophotometry (without reagent), and turbidimetry are linear. Linear range each method respectively at a concentration were (211.36-747.08); (16.000-146.434); and (1.8521-6.1717) ppm. The detection limit of each method successively were 53.6028; 0.5833; and 0.2723 ppm. Limit of quantitation each method successively were 66.9948; 1.9443; and 0.8068 ppm. Spectrophotometric analysis method cyclamate with hypochlorite reagent had good precision and accuracy. Ultra violet  spectrophotometric analysis method of cyclamate have a good precision but the accuracy was not good. Turbidimetric methods  analysis of cyclamate had  precision and accuracy were not good.Keywords:   method validation, spectrophotometry, turbidimetry, cyclamate